2018
DOI: 10.1016/j.advms.2017.05.003
|View full text |Cite
|
Sign up to set email alerts
|

Impact of intervention on metabolic outcomes among dropouts with type 2 diabetes

Abstract: Dropouts with T2D were difficult to bring back to the public health care system, especially men under the age of 60 years. Dropouts who participated in the intervention showed improvements in several metabolic outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…Although T2D is significant in view of public health [20] studies concerning how previous dropouts from T2D care use health services do not exist. According to our previous study findings from this same study cohort, these dropouts are challenging to bring back to the health care system; even when trained diabetes nurses contacted them personally, only one third were reattached [6]. To the best of our knowledge, studies focusing upon the importance of number of contacts between pre-vious dropouts and health care professionals in relation to glycaemic control are missing.…”
Section: Discussionmentioning
confidence: 89%
See 3 more Smart Citations
“…Although T2D is significant in view of public health [20] studies concerning how previous dropouts from T2D care use health services do not exist. According to our previous study findings from this same study cohort, these dropouts are challenging to bring back to the health care system; even when trained diabetes nurses contacted them personally, only one third were reattached [6]. To the best of our knowledge, studies focusing upon the importance of number of contacts between pre-vious dropouts and health care professionals in relation to glycaemic control are missing.…”
Section: Discussionmentioning
confidence: 89%
“…According to our study findings, one in ten patients with T2D was a dropout from the public primary diabetes health care system [5]. Further, the dropouts with T2D were difficult to bring back to the system [6]. Those who had poor glycaemic control and were successfully re-attached to the diabetes treatment system (e.g.…”
Section: Introductionmentioning
confidence: 90%
See 2 more Smart Citations
“…Previous study findings have shown that in the public primary health-care system, 1 in 10 patients with T2D is an "LTF" [4]. Although "LTFs" with T2D are generally difficult to bring back into the system, those with poor glycaemic control and who are successfully re-attached to the diabetes treatment system seem to benefit from being recalled [5]. Further, this subgroup of "LTFs" with T2D seems to benefit, at least glycaemic control improves, from intensive communication and counselling with the health-care professionals [6].…”
Section: Introductionmentioning
confidence: 99%